Effects of curcumin on the bioavailability of dioxin-like pollutants in rats - Delei Cai (Nature Portfolio, 2021)
Abstract The effects of curcumin on the bioavailability of polychlorinated dibenzo-p-dioxins/furans (PCDD/Fs) and dioxin-like polychlorinated biphenyls (DL-PCBs) were investigated in Sprague–Dawley rats. Tetra- and penta-chlorinated PCDFs had the lowest bioavailability and hexa-chlorinated PCDD/Fs had the highest, while there was no obvious change in that of DL-PCBs. Curcumin markedly reduced the toxic equivalent (TEQ) of PCDD/Fs in rats, illustrating the potential to competitively inhibit absorption of PCDD/Fs by the epithelial cells of the small intestine due to the similar chemical structure (diphenyl) between curcumin and PCDD/Fs. Moreover, curcumin lowered the TEQ of DL-PCBs in the liver of male rats, but not female rats. The significant decrease in the bioavailability of PCDD/Fs and DL-PCBs demonstrates the potential detoxification mechanisms of curcumin.